CA-125 KELIM as a Potential Complementary Tool for Predicting Veliparib Benefit: An Exploratory Analysis From the VELIA/GOG-3005 Study. Issue 1 (1st January 2023) - You, Benoit; Sehgal, Vasudha; Hosmane, Balakrishna; Huang, Xin; Ansell, Peter J.; Dinh, Minh H.; Bell-McGuinn, Katherine; Luo, Xizhi; Fleming, Gini F.; Friedlander, Michael; Bookman, Michael A.; Moore, Kathleen N.; et al.
Abstract : PURPOSE: In VELIA trial, veliparib combined with carboplatin-paclitaxel, followed by maintenance (veliparib-throughout) was associated with improved progression-free survival (PFS) compared with carboplatin-paclitaxel alone in patients with high-grade ovarian carcinomas. We explored the prognostic value of the modeled cancer antigen (CA)-125 elimination rate constant K (KELIM), which is known to be an indicator of the intrinsic tumor chemosensitivity (the faster the rate of CA-125 decline, the higher the KELIM and the higher the chemosensitivity), and its association with benefit from veliparib. PATIENTS AND METHODS: Individual KELIM values were estimated from longitudinal CA-125 kinetics. Patients were categorized as having favorable (≥ median) or unfavorable (< median) KELIM. The prognostic value of KELIM for veliparib-related PFS benefit was explored in cohorts treated with primary or interval debulking surgery, according to the surgery completeness, the disease progression risk group, and the homologous recombination (HR) status ( BRCA mutation, HR deficiency [HRD], or HR proficiency [HRP]). RESULTS: The data from 854 of 1, 140 enrolled patients were analyzed (primary debulking surgery, n = 700; interval debulking surgery, n = 154). Increasing KELIM values were associated with higher benefit from veliparib in HRD cancer, as were decreasing KELIM values in HRP cancer. The highest PFS benefit from veliparib was observed in patients with both favorable KELIM and BRCA mutation (hazard ratio, 0.28; 95% CI, 0.13 to 0.61) or BRCA wild-type HRD cancer (hazard ratio, 0.43; 95% CI, 0.26 to 0.70), consistent with the association between poly (adenosine diphosphate-ribose) polymerase inhibitor efficacy and platinum sensitivity. In contrast, seventy-four percent of patients with a BRCA mutation and unfavorable KELIM progressed within 18 months while on veliparib. The patients with HRP cancer and unfavorable KELIM might have benefited from the veliparib chemosensitizing effect. CONCLUSION: In addition to HRD/ BRCA status, the tumor primary chemosensitivity observed during the first-line chemotherapy might be another complementary determinant of poly (adenosine diphosphate-ribose) polymerase inhibitor efficacy.